Characterization of the thermal performance of outdoor telecommunication cabinets - Silva, Pedro Dinho da (2019)
The growing use of telecommunication technologies has led the industry to develop infrastructure to support this progress. The outer telecommunications cabinets are part of the Base Transceiver Station allowing to accommodate and protect from outer adverse conditions a set of electronic equipment needed to operate the mobile communication network. This kind of cabinets should have a proper thermal performance to ensure indoor air temperature below 55°C to avoid exceeding the maximum operating temperature of the electronic equipment. This work describes the analysis of the thermal performance of an outdoor telecommunication cabinet using the computational tool DesignBuilder. The simulation results are compared to the experimental data collected in real cabinet under normal operating conditions. The simulation results show that the air temperature predicted by the model is closer to the temperature measured experimentally inside the cabinet particularly when the weather data files of the computational model have a similar behavior to the actual weather data. Numerical studies show that the use of mechanical ventilation is effective in the extraction of heat generated inside the cabinet. However, there is a limit beyond which increasing the air flow rate does not result in a significant decrease of the cabinet air temperature. The studies also show the importance of the radiant properties and the geographical location of the cabinet. High values of the outer surface cabinet emissivity impair the thermal performance of the cabinet during the day and for some locations, an operational mechanical ventilation system may not be enough to maintain the indoor air temperature below 55°C. Overall, the use of DesignBuilder proved to be very effective for characterizing the thermal performance of telecommunications outdoor cabinets.